Rethinking theoretical schools and circles in the 20th-century humanities - Gramigna, Remo (Sign Systems Studies, 2016)
Review of Theoretical Schools and Circles in the Twentieth-Century Humanities: Literary Theory, History, Philosophy, ed. by Marina Grishakova and Silvi Salupere. New York, London: Routledge, 2015. 287 pp.